2015
DOI: 10.1155/2015/872035
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of Hollow Mesoporous Silica Nanoparticles for Improved 5‐FU Loading

Abstract: Hollow mesoporous silica nanoparticles were successfully fabricated and functionalized with appropriate silanes. After modifications, amine, carboxyl, cyano, and methyl groups were grafted onto the nanoparticles and all functionalized hollow mesoporous silica nanoparticles maintained a spherical and hollow structure with a mean diameter of ~120 nm and a shell thickness of ~10 nm. The loading capacity of the hollow mesoporous silica nanoaprticles to the anticancer drug, 5-fluorouracil, can be controlled via pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 36 publications
2
53
0
Order By: Relevance
“…The nanostructure‐containing COOH exhibited the highest loading efficiency because of bonding between this negatively charged species and the positively charged doxycycline (Sun et al, ). Another study reported the loading of anticancer drug 5‐fluorouracil to H‐MPSNPs containing different functional groups such as CN, COOH, and NH 2 (She et al, ). The nanocarrier with NH 2 showed the highest loading efficiency because both 5‐fluorouracil and NH 2 have similar lipophilic nature.…”
Section: Surface Modification Of Mpsnpsmentioning
confidence: 99%
See 1 more Smart Citation
“…The nanostructure‐containing COOH exhibited the highest loading efficiency because of bonding between this negatively charged species and the positively charged doxycycline (Sun et al, ). Another study reported the loading of anticancer drug 5‐fluorouracil to H‐MPSNPs containing different functional groups such as CN, COOH, and NH 2 (She et al, ). The nanocarrier with NH 2 showed the highest loading efficiency because both 5‐fluorouracil and NH 2 have similar lipophilic nature.…”
Section: Surface Modification Of Mpsnpsmentioning
confidence: 99%
“…The nanocarrier with NH 2 showed the highest loading efficiency because both 5‐fluorouracil and NH 2 have similar lipophilic nature. In addition, an increase in 5‐fluorouracil loading was observed in alkaline condition due to the enhanced electrostatic attraction of protonated 5‐fluorouracil with the nanoparticles (She et al, ).…”
Section: Surface Modification Of Mpsnpsmentioning
confidence: 99%
“…Outer decoration of MSNs with disulphide linked polymer to achieve the redox responsive release of drug has been done by author Liu R, et al 78 A variety of functional group or moieties can be attached on the surface of MSNs by either of the above mentioned techniques as listed in the Table 2. 11,[79][80][81][82][83][84][85][86][87][88][89][90] Backfilling strategy is another approach used for MSNs fabrication. It is a simple approach to introduce active molecules into the empty pores of mesostructured silica wherein, these empty pores are exposed to the solution or vapour of active molecules and are allowed to diffuse.…”
Section: Post Synthesis Strategymentioning
confidence: 99%
“…221 A drug delivery system for 5-FU should be small in size, able to carry the required amount of drug without excessive loading of cells with the drug to be liberated at the target site and be able to transport the drug in its parent form. 220 Literature precedent shows that drug delivery systems such as PLGA 222 and chitosan 57,223 polymers, methacrylic based and other nanogels, [224][225] zeolites 226 and mesoporous silica 221,[227][228] have been used as potential host systems for 5-FU delivery.…”
Section: Introductionmentioning
confidence: 99%
“…With each addition of TEOS, the formation of the silica adds to the previously formed Using volume/volume ratios of 5:5 water/ acetone to 1:9 water/acetone, surprisingly it was discovered that even though pure acetone by itself is a poor solvent of 5-FU, with the increase of acetone in the water/acetone mixture the solubility of 5-FU increased and as result, the loading efficiency of 5-FU into m-MCM-41 increased (Table 8. is protonated due to a favorable electrostatic interaction between the protonated amine and the 5-FU. 221,227,233 In an attempt to understand these differences and to explore the impact of loading with different solvents on the release properties, these three solvent systems (water, water/acetone and DMSO) were further investigated using FTIR and solid state NMR, as well as 5-FU release studies under physiological conditions.…”
mentioning
confidence: 99%